The Role of Agriculture in Women’s Economic Empowerment in Wau County, Western Bahr-El-Ghazal, South Sudan - Jackson, Openi Jame; Sendawula, Noah (Advances in Social Sciences Research Journal, 2023)
The study examined the role of agriculture in women's economic empowerment in Wau County, Western Bahr - El - Ghazal state, South Sudan. The objectives of the study were to examine the influence of agricultural extension services on women's economic empowerment in Wau Country of Western Bahr-El-Ghazal, South Sudan; to assess the effect of climate-smart agriculture on women's economic empowerment in Wau County of Western Bahr-El-Ghazal, South Sudan; and to establish the effect of gender equity in agriculture on women economic empowerment in Wau County of Western Bahr-El-Ghazal, South Sudan. The study applied a cross-sectional survey research design, along with both quantitative and qualitative approaches. 200 participants were recruited for the study using both simple random and purposive sampling techniques and both self-administered questionnaires and interview guide instruments. Quantitative data were analyzed using descriptive statistical analysis with help of SPSS Version 21 and qualitative data were analyzed using both thematic analysis and content analysis. It is found that women farmers in Wau Country of Western Bahr-El-Ghazal receive different extension services, research-based agricultural information to help them in their agricultural activities, access productivity-enhancing technologies through extension services through government agricultural programs and other NGOs who work to empower women, women farmers have not been involved in co-head to get information on agriculture best practices through extension services that leave them behind regarding economic empowerment and women farmers receive information to operate new agricultural equipment to improve the agricultural productivity to their income.